Predictors of Onset of Wheezing in Grain Elevator Workers - Punam Pahwa; Ambikaipakan Senthilselvan; Helen H McDuffie; James A Dosman (Canadian Respiratory Journal)
A longitudinal study of Canadian grain elevator workers over a 12-year period was conducted. Data on respiratory symptoms and pulmonary function tests were collected once every three years as part of the Grain Dust Medical Surveillance Program started by Labour Canada in 1978; each three-year interval was called a 'cycle'. Of workers who had two or more observations, 1848 subjects (67.2%) were free of respiratory symptoms (wheeze, dyspnea, cough or sputum) at the baseline (cycle II). Predictors of first episode of wheezing were examined in these symptoms-free grain workers. Baseline mean age ± SD of the grain workers was 34.0±11.4 years and mean duration of work in the industry was 9.9±8.7 years. Of the 1848 symptoms-free grain workers at cycle II, 203 (11.0%) subsequently reported wheezing during the study. Cox's proportional hazards model for analysis of survival data was used to determine significant predictors of first episode of wheezing. Significant predictors for first episode of wheezing were current smoking (relative risk [RR] 2.33; 95% CI 1.63 to 3.33; P<0.0001) and baseline forced expiratory volume in 1 s to forced vital capacity ratio [RR 0.02; 95% CI 0.003 to 0.20; P<0.0001). Baseline pulmonary function measurements and smoking habits appear to be important predictors of future development of asthma-like symptoms in grain elevator workers.